Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/cmdc.201100054
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Xanthine Oxidase by Thiosemicarbazones, Hydrazones and Dithiocarbazates Derived from Hydroxy‐Substituted Benzaldehydes

Abstract: Nonpurine xanthine oxidoreductase (XOR) inhibitors represent important alternatives to the purine analogue allopurinol, which is still the most widely used drug in the treatment of conditions associated with elevated uric acid levels in the blood. By condensing mono-, di- and trihydroxybenzaldehydes with aromatic thiosemicarbazides, aryl hydrazides and dithiocarbazates, three series of structurally related Schiff bases were synthesised, characterised and tested for XOR inhibitory activity. Hydroxy substitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 69 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Selected bond lengths and angles and crystallographic data are summarized in Tables 1 and 2, respectively. The crystal structures confirmed that the thiosemicarb- [18,27,28,[37][38][39][40] The crystals consist of racemic mixtures of OC-6-24-Aand OC-6-24-C-configured [35,36] enantiomers. The complexes crystallize in centrosymmetric space groups…”
Section: X-ray Structuresmentioning
confidence: 73%
See 1 more Smart Citation
“…Selected bond lengths and angles and crystallographic data are summarized in Tables 1 and 2, respectively. The crystal structures confirmed that the thiosemicarb- [18,27,28,[37][38][39][40] The crystals consist of racemic mixtures of OC-6-24-Aand OC-6-24-C-configured [35,36] enantiomers. The complexes crystallize in centrosymmetric space groups…”
Section: X-ray Structuresmentioning
confidence: 73%
“…[24] In particular, thiosemicarbazones derived from salicylaldehydes allow a systematic investigation of the effect of electron-withdrawing groups (EWGs) or electron-donating groups (EDGs) on the electronic properties of a coordinated molybdenum center. It was found that these electronic trends are reflected in the spectroscopic properties of the molybdenum complexes formed, [18,25] and in their catalytic, [26] biological, [27,28] and pharmacological properties. [29,30] Here we present the synthesis, characterization and catalytic OAT activity of a series of cis-dioxomolybdenum(VI) complexes with structurally related tridentate thiosemicarbazone ligands (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…These drawbacks have prompted the search for non-purine based XO inhibitors that lead to the discovery of recently approved drug Febuxostat 14 and its derivatives Piraxostat 15 and FYX-051 16 . Other classes of non-purine XO inhibitors reported in recent years include azaflavones 17 , pyrazolines 18 , acetamides 19 , naphthopyrans 20 , heteroaryl pyrimidinones 21 , isocytosines 22 , thiadiazolopyrimidones 23 , benzaldehydes 24 , and xanthones 25 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, thiosemicarbazones derived from salicylaldehydes allow a systematic investigation of the effect of electron‐withdrawing groups (EWGs) or electron‐donating groups (EDGs) on the electronic properties of a coordinated molybdenum center. It was found that these electronic trends are reflected in the spectroscopic properties of the molybdenum complexes formed,18,25 and in their catalytic,26 biological,27,28 and pharmacological properties 29,30…”
Section: Introductionmentioning
confidence: 99%